A Best-Selling Hebrew Book of the Modern Era : The Book of the Covenant of Pinhas Hurwitz and Its Remarkable Legacy - Ruderman, David B. (Book collections on Project MUSE., 2014)
"This manuscript is a literary history of The Book of Covenant, an encyclopedic work of science, philosophy, and ethics written in the late-eighteenth century by Jewish philosopher and polymath Pinhas Hurwitz. Ruderman explores the reasons for the book's huge popularity--it has been republished in forty editions in the last century--as well as its lasting influence on Jewish and kabbalistic thought, and its important place in Jewish society's confrontation with modernity"--